Graft‐versus‐host disease after autologous stem cell transplantation in a recipient who underwent allogeneic stem cell transplantation 20 years earlier - Osamu Imataki; Shunsuke Yoshida; Tomoya Ishida; Haruyuki Fujita; Makiko Uemura (eJHaem, 2024)
Abstract A literature review does not provide information about the safety of autologous hematopoietic stem cell transplantation (HSCT) in a recipient who has previously received allogeneic HSCT. We treated a 69‐year‐old woman with diffuse large B cell lymphoma. The patient received autologous stem cell transplantation (ASCT) in the second complete remission of malignant lymphoma. The patient had undergone allogeneic hematopoietic SCT (allo‐HSCT) for chronic myeloid leukemia 20 years ago. Chronic myeloid leukemia had been in complete remission for the previous 20 years. Thus, the patient received autologous and allogenic HSCT 20 years apart. ASCT involves the patient receiving “self” hematopoietic cells from an allogeneic donor. In other words, this is immunologically the second allo‐HSCT. The allo‐HSCT 20 years ago was undergone by a related healthy brother, a human leukocyte antigen (HLA) 8/8 full matched donor. The conditioning regimen was reduced‐intensity consisting of fludarabine and busulfan. The patient did not experience acute or chronic graft‐versus‐host disease (GVHD) after allo‐HSCT. The second transplantation, ASCT was performed to the MEAM conditioning regimen. Engraftment was uneventful, and complete donor chimerism had been achieved even after ASCT. She suffered from an acute gastric mucosal lesion 52 days after ASCT. Pathological finding of gastric mucosa was nonspecific acute gastritis with significant neutrophil infiltration. Sex chromosome analysis of gastric mucosa demonstrated that mucosal cells had XX signals, whereas infiltrating neutrophils had XY signals. We speculated the patient onset of an acute gastric GVHD in this recipient after the second transplantation. This case remarked infiltration of neutrophils triggered GVHD reaction by resetting allogeneic immune reaction after the second transplantation. We describe a rare occurrence of GVHD reaction in a recipient of ASCT following allo‐HSCT.